Humanized single-domain antibody targeting HER2 enhances function of chimeric antigen receptor T cells - Zheng, Rui; Chen, Yuankun; Zhang, Yiting; Liang, Sixin; Zhao, Xiaojuan; Wang, Yiyi; Wang, Pengju; Meng, Ruotong; Yang, Angang; Yan, Bo (Frontiers in Immunology, 2023)
Chimeric antigen receptors (CARs) can redirect T cells against antigen-expressing tumors, and each component plays an important role in the function and anti-tumor efficacy. It has been reported that using human sequences or a low affinity of CAR single-chain variable fragments (scFvs) in the CAR binding domains is a potential way to enhance the function of CAR-T cells. However, it remains largely unknown how a lower affinity of CARs using humanized scFvs affects the function of CAR-T cells until recently. Here, we used different humanized anti-HER2 antibodies as the extracellular domain of CARs and further constructed a series of the CAR-T cells with different affinity. We have observed that moderately reducing the affinity of CARs (light chain variable domain (VL)-based CAR-T) could maintain the anti-tumor efficacy, and improved the safety of CAR therapy both in vitro and in vivo compared with high-affinity CAR-T cells. Moreover, T cells expressing the VL domain only antibody exhibited long-lasting tumor elimination capability after multiple challenges in vitro, longer 2 persistence and lower cytokine levels in vivo. Our findings provide an alternative option for CAR-T optimization with the potential to widen the use of CAR T cells.